Restructuring State-Society Relations under the Rule of the AKP through Diplomacy - Shaimaa Magued (Akademik İncelemeler Dergisi)
Unlike his predecessors, the AKP refused to be at the crossroads between Secularism and Islamism as two ideological antonyms by restructuring the State-society relations. The efforts of conciliation on the national scene are not enough in integrating politics and alleviating polarization between these two antagonistic tendencies. The simultaneous recourse to a balanced diplomacy is then considered as an effective means in ensuring stability, transcending the establishment resistance and normalizing the Turkish politics through the reformulation of the centre and the acceptation of the marginalized groups as legitimate actors both on the domestic and the external levels.